(untitled) (Research, Society and Development, 2021)
We analyzed the diet of Bryconamericus microcephalus, the most abundant species in the streams of the Cubatão river basin. The specimens were collected with electric fishing in 2016, in ten different points of the basin, within the UC - Itutinga-Pilões Nucleus. The fish were identified, measured, weighed and dissected. Stomachs with food were removed for diet analysis by the Degree of Food Preference. The diet was analyzed through the relationship of the Shannon-Weaver diversity index and the characteristics of the individuals. The relationship between food items and species length was analyzed by a Pearson correlation test, and the relationships of qualitative items (sex and gonadal maturation stages) by a two-way Analysis of Variance. 211 individuals were sampled, 43 males, 66 females and 102 immature. We analyzed 45 stomachs, in which we recorded 20 items, classifying the studied population as omnivorous, with the main consumption of immature forms of insects. The record of most items was classified as occasional, reflecting the opportunistic character of the species, with consumption of allochthonous items, showing the strong relationship with the riparian forest. We emphasize, therefore, that the analysis of the diet allows a better understanding of the ecology of the species and its conservation.